(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Rational use of corticosteroids is very essential for improving patient safety on long term use. The present study aimed to study the prescribing usage pattern of corticosteroids in a tertiary care hospital. A prospective observational study was conducted in the department of dermatology, gynecology and general medicine in a tertiary care teaching hospital for the period of 6 months (August-February). All patients receiving any category of Steroid therapy were included and the prescribing and tapering pattern of steroids were reviewed. Prescribing pattern was observed and analysed in 132 participants during the study period. Cases were collected from the departments of Dermatology, General Medicine, Pediatrics and Gynecology in Gandhi Hospital, Secunderabad. All the prescriptions containing steroids were included in this study and the parameters evaluated were gender distribution, age of the patients, types of steroids according to the route of administration, number of prescribed daily dose (PDD) where compared with defined daily dose (DDD). In the collected 132 cases, 162 times corticosteroids were prescribed. The steroid utilization was found to be more in female patients, the maximum number of cases with corticosteroids was found in Dermatology department (39.4%). Particularly Injection Dexamethasone (24.7%) and Tablet Prednisolone (24.7%) are mostly prescribed. Most drugs were prescribed rationally although some factors like improper history, drug administration time and tapering were deviating away from rationality. Although most of the drugs were prescribed rationally, involvement of a Clinical pharmacist in patient care can help in more rational prescribing along with prevention and early detection of ADRs which can directly promote drug safety and better patient outcomes.